Functional and Clinical Characteristics of Cell Adhesion Molecule CADM1 in Cancer - Li, Hongxu; Gao, Jie; Zhang, Shuijun (Frontiers in Cell and Developmental Biology, 2021)
The cell adhesion molecule CADM1, which participates in cell adhesion and signal transduction, has a regulatory effect on the development of tumors. CADM1 is often involved in malignant tumors of multiple organ systems, such as the respiratory and digestive systems. Upregulated CADM1 promotes tumor cell apoptosis, and inhibits malignant proliferation. Along with cell cycle-related proteins, it participates in regulating signaling pathways, such as EMT, STAT3, and AKT, and plays an important role in inhibiting invasion and migration. Considering clinical characteristics, low CADM1 expression is associated with aggressive tumors and poor prognosis. In addition, some long non-coding RNAs (lncRNAs) or miRNAs directly or indirectly act on CADM1 to regulate tumor growth and motility. Interestingly, CADM1 function differs in adult T-cell leukemia/lymphoma (ATLL), and NF-κB is thought to be involved in this process. Taken together, CADM1 could be a potential biomarker for early diagnosis, and a target for cancer treatment in future clinical practices.